DAYA HAMBAT EKSTRAK ETANOL KULIT BUAH PISANG KEPOK MENTAH (Musa paradisiaca forma typica) TERHADAP PERTUMBUHAN Escherichia coli SECARA IN VITRO¬ - Novia Ariani; Norjannah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
Banana plants is the most one that produce and used by Indonesian people. Banana plants has a lot of kind, and the one is kepok banana. Kepok banana peel has used to make some kind of foods but for drug use is still limited whereas in banana peel contains secondary metabolites flavonoids, alkaloids, saponins and tannins has antibacterial activity. The purpose of this research was to determine resistivity of peel extract of raw banana kepok (Musa paradisiaca forma typica) on the growth of Escherichia coli in vitro. This type of research is non experimental with the method of wells conducted in the laboratory of Microbiology of Pharmacy Academy of ISFI Banjarmasin. The sampling used by purposive sampling technique with certain criteria. To determination of resistibility saw the transparent zone around the well. The results of this research showed that bark extract of raw banana peel extract had inhibitory power to growth of Escherichia coli in vitro.